High Energy Digestible Fiber-based Diets Improve Efficiency in Growing Heifers - T. Spore; S. P. Montgomery; G. A. Hanzlicek; K. T. Cavalli; W. R. Hollenbeck; R. N. Wahl; E. Titgemeyer; Christopher Vahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
An inherent challenge of long hauled, highly stressed calves is decreased feed intake upon destination arrival. Highly stressed, newly received stocker calves not consuming adequate amounts of energy are prone to a variety of disorders such as Bovine Respiratory Disease Complex and decreased performance throughout the feeding period. One mechanism that can be used to increase energy intake upon arrival is to make the diet more energy dense. Often times, this is accomplished by the addition of cereal grains high in fermentable carbohydrate including starch. Unfortunately, this has also been linked to increasing morbidity due to metabolic disorders. The goal of this study was to analyze the effects of limit-fed diets containing increasing amounts of energy from highly digestible fiber in by-product feeds on health and performance of newly received stocker calves.
Keywords: wet corn gluten feed; health; limit-feeding